International students’ empathy and sensation seeking traits as the antecedents of motivation to engage in intercultural communication - Nadeem, Muhammad Umar; Mohammed, Rosli; Dalib, Syarizan (University of Central Punjab, 2018)
From the Non-Western context of Malaysia, this study aims to address the influence of empathy and sensation seeking of international students on their motivation to engage in intercultural communication (MTEIIC). Earlier, the investigators tend to focus more on determining the predictors of Intercultural Communication Competence (ICC) as of MTEIIC. The relationships of selected trait-like factors of MTEIIC is subjected to Western context and considered these factors have the potential to translate well on diverse cultures. Thus, this study considers empathy and sensation seeking and addressed on the Non-Western context of Malaysia. Through simple random sampling, the data was collected from the international students of University Utara Malaysia by incorporating survey technique. The data was analyzed in SPSS and AMOS by incorporating Structural Equation Modeling (SEM) technique. The findings of the study empirically justified that empathy and sensation seeking are the significant antecedents of MTEIIC in the Non-Western context of Malaysia. Furthermore, the culture-general nature of selected variables is also validated from the findings of this study. It is evident that international students of Malaysia are having empathetic and sensation seeking traits that are favorable for MTEIIC.